pengetahuan ibu tentang ASI Eksk Pemberian ASI Eksklusif: HUBUNGAN TINGKAT PENGETAHUAN IBU TENTANG PEMBERIAN MP-ASI DENGAN KEJADIAN DIARE PADA ANAK USIA 6-24 BULAN - Yulnefia Yulnefia; Ari Diansyah; Athirah Puteri Hanani (LPPM Universitas Abdurrab, 2025)
Diarrhea is a condition of abnormal excretion of stool characterized by an increase in volume, dilution, and frequency of bowel movements more than 3 times a day. External factors of diarrhea in children are the type and form of MP-ASI that are not suitable for age, unhygienic cutlery for children, and poor hygiene or sanitation. To increase mother's knowledge about giving MP-ASI properly and reduce the incidence of diarrhea, it is necessary to have better access to handling it, namely by counseling and demonstrating about the right time to give MP-ASI. This research method uses an analytic observation research design with a cross sectional design. The sampling technique in this study was using the Accidental Sampling technique with a total of 80 samples obtained. It was found that there was a significant relationship between the level of mother's knowledge about giving MP-ASI and the incidence of diarrhea in children aged 6-24 months in the working area of the Sidomulyo Inpatient Health Center, Tampan District, Pekanbaru City with a Fisher Exact Test value of 0.005.